The antecedents of adolescents' climate change concern in Cambodia - Rouhiainen, Henna; Haanpää, Leena (International research in geographical and environmental education, 2024)
Understanding climate change concern among adolescents is considered a useful strategy for building public engagement with climate change. However, the psychological and sociodemographic antecedents of climate change concern have been studied mainly with Western adults. We used structural equation modeling (SEM) to gain insights into the factors predicting climate change concern among adolescents in Cambodia to be used to support the planning of climate related education. The results of a survey with students in grades 7-9 (N = 389) show that ecological worldview-or belief in an ecocrisis-is the strongest predictor of climate change concern among Cambodian adolescents. Altruistic environmental concern is associated with the strength of the ecological worldview. Building understanding of the human impact on climate and reflection on altruistic motives for environmental action may be good focal points for climate change education in Cambodia, however more research is needed to better understand climate change concern and its individual and cultural predictors in Cambodia and elsewhere outside the West.